DEVELOPMENT OF ECOSYSTEM DANCE AUDIOBOOK MEDIA TO ENHANCE THE CREATIVITY OF ELEMENTARY SCHOOL STUDENTS - Gibran Fadil Nugroho; Deasylina da Ary (Universitas Labuhanbatu, 2026)
Purpose- This study aimed to develop, determine the feasibility, and measure the effectiveness of ecosystem dance audiobook media in improving the creativity of fourth-grade elementary school students in dance learning.Methodology- The study employed a Research and Development (R&D) approach using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SDN 2 Pagergunung, Kendal Regency, Central Java, involving 14 fourth-grade students, one classroom teacher, and expert validators. Data were collected through observations, interviews, questionnaires, validation sheets, documentation, and pretest-posttest assessments. Qualitative data were analyzed descriptively, while quantitative data were analyzed using the Shapiro–Wilk normality test, paired sample t-test, and N-gain test with the assistance of SPSS version 29.Findings- The validation results showed that the media was categorized as highly feasible, with scores of 95.7% from material experts and 94% from media experts. These findings are supported by teacher and student responses, which were highly positive at 93% and 92.6%, respectively. The paired-samples t-test showed a p-value of 0.000 (<0.05), indicating a significant improvement in learning outcomes. This result is further supported by the N-gain score of 0.58, which indicates a moderate level of effectiveness. Therefore, the ecosystem dance audiobook media was proven to be feasible, practical, and effective in enhancing students’ creativity in dance learning.Contribution- This research contributes to the development of dance-learning media that encourage student activity through an audio and book approach for grade 4 materials. It integrates dance and science maps, strengthening students' psychomotor skills. In addition, this research offers teachers an alternative literacy learning media that is creative, interesting, and aligned with students' learning characteristics.